2022
DOI: 10.1177/21501351221119494
|View full text |Cite
|
Sign up to set email alerts
|

Ross Procedure in Neonate and Infant Populations: A Meta-Analysis Review

Abstract: Objective This study aims to perform a meta-analysis of early and late outcomes of the Ross/Ross-Konno procedures in neonates/infants. Methods A meta-analysis was performed in accordance with PRISMA guidelines. We used Ovid versions of MEDLINE/PubMed for relevant studies and included those that reported Ross/Ross-Konno operations in neonates/infants and at least one of the predetermined clinical outcomes. I2 and double arcsine methods assessed the heterogeneity between pooled estimates. We used a random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Overall, 25 observational studies with a total of 2737 patients were included. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 By design, all included studies had a ROBINS I score in the low or moderate risk of bias category ( Supplemental Table S1 ).
Figure 1 Flow chart of the literature search.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 25 observational studies with a total of 2737 patients were included. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 By design, all included studies had a ROBINS I score in the low or moderate risk of bias category ( Supplemental Table S1 ).
Figure 1 Flow chart of the literature search.
…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 Consistently, a recent study in neonates (<30 days of age) reported high levels of early (24%) and late (43%) mortality after the Ross procedure. 3 Although outcomes have improved over time, 18 several studies including an analysis using the Society for Thoracic Surgeons Congenital Heart Disease Database 18 and a recent meta-analysis 19 in children reported significant associations between low-volume centres (defined as <4 cases/y in the Society for Thoracic Surgeons study) and higher mortality, particularly among neonates. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AVR still has many limitations in children such as rapid deterioration ( 3 , 4 ) in bioprosthetic valves, high risk of anticoagulation-related complications ( 5 , 6 ) in mechanical valves as well as size mismatch in young patients with small annuluses ( 7 ). The Ross procedure is a good option for young children but it is not widely applied in developing countries due to relatively high mortality, lack of valved conduit, and risk of impacting both semilunar valves ( 8 , 9 ). Partial heart transplantation contributes a new approach to solve the problem, allowing annular growth, but the risks from immunosuppression remain concern ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many of these complex patients require aortic valve and LVOT intervention in the neonatal and infant period when the procedural risk of a Ross-Konno is highest. 2 There is however substantial heterogeneity in Ross procedure outcomes in this age range 6 and more recently excellent outcomes have been demonstrated in the contemporary era. 7 Despite potentially higher procedural risk, long-term pulmonary autograft longevity may be optimized by performing the Ross procedure in the neonatal and infant age range as the pulmonary root remains adapted to systemic pressures at this stage.…”
mentioning
confidence: 99%